2017
DOI: 10.1139/cjb-2016-0158
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of thermotolerance, chlorophyll fluorescence, and heat shock gene expression vary among fourBoecheraspecies andArabidopsis thaliana

Abstract: Thermotolerance is a property of all organisms, but owing to their sessile nature, this trait is particularly important in plants. Basal thermotolerance is based on inherent tolerance to heat stress. Acquired thermotolerance is attained through stress-induced gene expression, often of those genes encoding heat shock proteins (HSPs). Both basal and acquired thermotolerance have been extensively studied in model species such as Arabidopsis thaliana (L.) Heynh., but much less is known about thermotolerance in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Previous research has shown that B. depauperata is both more tolerant to high light and combined high light and high heat stress than is A. thaliana . Boechera depauperata can also maintain photosynthesis at higher temperatures ( Gallas and Waters 2015 ; Halter et al 2017 ). While the genes associated with photosystem II and photosystem repair did not have enough AS change to be included in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that B. depauperata is both more tolerant to high light and combined high light and high heat stress than is A. thaliana . Boechera depauperata can also maintain photosynthesis at higher temperatures ( Gallas and Waters 2015 ; Halter et al 2017 ). While the genes associated with photosystem II and photosystem repair did not have enough AS change to be included in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plants were grown, and basal and acquired heat stress experiments were conducted as described in ( Larkindale and Vierling 2008 ; Gallas and Waters 2015 ; Halter et al 2017 ). Basal and acquired heat stress experiments were conducted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basal heat tolerance (also called intrinsic heat tolerance) is the natural capacity of plants to tolerate heat by inherent factors. Acquired heat tolerance (also called adaptive heat tolerance) occurs after priming or acclimation triggered by a short pre-exposure to non-lethal heat [8]. The perception mechanisms mediating heat stress responses are still largely unknown and likely to be different from those associated with thermomorphogenesis [2,9].…”
Section: Introductionmentioning
confidence: 99%